Evaluation of the onset of failure under mechanical and thermal stresses on luting agent for metal-ceramic and metal crowns by finite element analysis - Hema Agnihotri; Naresh Bhatnagar; G Venugopal Rao; Veena Jain; Hari Parkash; Aswini Kumar Kar (Wolters Kluwer Medknow Publications, 2010)
Long-term clinical failures of cemented prosthesis depend, to a large extent, on the integrity of the luting agent. The causative factors that lead to microfracture and, hence, failure of the luting agents are the stresses acting inside the oral cavity. Therefore, the present study was designed to develop an understanding of the relationship between stresses in the tooth and the failure potential of the luting agent. Two-dimensional finite element stress analysis was performed on the mandibular second premolar. The behavior of zinc-phosphate and glass-ionomer were studied under different crowns (metal-ceramic and metal crown) and loading conditions (mechanical force of 450 N acting vertically over the occlusal surface, thermal loads of 60° and 0°C). It was observed from the study that failure threshold of the luting agent was influenced both by the elastic modulus of the luting agent and by the type of the crown.